Model Evaluasi Sumatif Dalam Mengevaluasi Program Pengenalan Kendaraan Di PAUD Nurul Hidayah - Ach Furqon Wiguna; Amna Annisa Pratiwi; Fasfa Ayu Utami; Vita Fatimah; Zakiyatunufus . (CV. ITTC INDONESIA, 2023)
The transportation environment is something that is inherent to every child including elements such as vehicles, which have a significant impact on children's awareness and understanding of the world they explore. Vehicle introduction program is one of the programs implemented by PAUD Nurul Hidayah. The summative evaluation conducted aims to evaluate the vehicle introduction program at PAUD Nurul Hidayah in order to assess the extent to which the program objectives have been achieved and assess the effectiveness of the program implementation. This evaluation uses a summative evaluation model and this research uses qualitative research methods. In its implementation, the program is implemented with various activities including vehicle introduction through visual media, singing together, visits to stations and ports, and coloring. Based on the results of the summative evaluation that has been carried out, the outputs resulting from this vehicle introduction program include children showing active participation, children have developed knowledge about vehicles, increasing children's skills and motor skills, increasing children's communication and language skills, increasing children's creativity, developing children's socio-emotional abilities, and creating participation and involvement of parents. Thus, this program is worth continuing and can be a reference in developing similar programs in other Early Childhood Education.